Functional Smart Dispersed Liquid Crystals for Nano- and Biophotonic Applications: Nanoparticles-Assisted Optical Bioimaging. (9th June 2016) - Kamanina, N. V.; Likhomanova, S. V.; Zubtcova, Yu. A.; Kamanin, A. A.; Pawlicka, A.
Abstract : Functional nematic liquid crystal structures doped with nano- and bioobjects have been investigated. The self-assembling features and the photorefractive parameters of the structured liquid crystals have been comparatively studied via microscopy and laser techniques. Fullerene, quantum dots, carbon nanotubes, DNA, and erythrocytes have been considered as the effective nano- and biosensitizers of the LC mesophase. The holographic recording technique based on four-wave mixing of the laser beams has been used to investigate the laser-induced change of the refractive index in the nano- and bioobjects-doped liquid crystal cells. The special accent has been given to novel nanostructured relief with vertically aligned carbon nanotubes at the interface: solid substrate-liquid crystal mesophase. It has been shown that this nanostructured relief influences the orienting ability of the liquid crystal molecules with good advantage. As a result, it provokes the orientation of the DNA. The modified functional liquid crystal materials have been proposed as the perspective systems for both the photonics and biology as well as the medical applications.